HUBUNGAN ANTARA KEMATANGAN EMOSI DENGAN PERILAKU AGRESIF PADA SISWA SMK - Deis Sabintoe; Christiana Soetjiningsih (PSIKOLOGI KONSELING, 2020)
This study aims to determine the relationship between emotional maturity with aggressive behavior in vocational students. This research was conducted on SMK students of class XI. The research sample of 63 students with saturated sampling technique. This type of research used in this study is a quantitative study with data collection procedures using a psychological scale that is the scale of emotional maturity from Katkhovsky and Gorlow (1976) totaling 47 items and the scale of aggressive behavior from Buss and Perry (1992) totaling 29 items. Statistical data analysis using Pearson Product Moment Analysis Test with the help of SPSS Statistics 16.0 for windows. The correlation coefficient obtained was -0.240 with a significance value of 0.029 (p <0.05). These results indicate that the hypothesis proposed by researchers, namely there is a negative relationship between emotional maturity with aggressive behavior in vocational students can be accepted. The negative correlation coefficient value indicates that the direction of the relationship between the two variables is negative, meaning that the higher the emotional maturity, the lower the aggressive behavior.